Getting Attention, Keeping Attention and Measuring Attention in the Age of Information Overload: Billboard and Poster Advertising in the 21st Century - White, Paul Joseph (Auckland University of Technology, 2012)
This thesis examines how advertising posters and billboards continue to communicate successfully in the 21st century despite, and in conjunction with, the emergence of a plethora of new communications technologies that make increasing demands on people’s time and attention. The thesis first establishes how billboards and posters gained attention and mediated messages prior to this present age of information overload by analysing the famous Lord Kitchener British army recruitment poster, created in 1914. The thesis then compares marketing communications mediated by conventional posters and billboards with those employing a convergence of old and new technologies; namely, three NZ Army interactive recruitment posters created in 2007, a billboard for Deadline Couriers also created in 2007 and a road safety billboard for Rodney District Council created in 2008. Where most studies approach the analysis of advertising and marketing communications texts from either a semiotic standpoint or social discourse perspective, this thesis combines both semiotics (Kress and Van Leeuwen 1996) and mediated and multimodal discourse analysis (Scollon, 1998, Norris 2004, Jones, 2005, Jewitt, 2010). This approach reveals a demonstrable link between the semiotic structure of posters and billboards and the quality of attention a person must employ in order to successfully receive the messages they mediate. The thesis challenges conventional marketing theory (Arens, 2004, Drewniarny and Jewler, 2011) with regard to poster and billboard design and reception. It also confronts the growing belief that, in the wake of an unprecedented growth in new communications technologies, society may be in danger of developing some kind of attention deficit disorder (Sacharin, 2001). The thesis finds that new communications technologies can and do transform posters and billboards as mediational means in significant ways. The thesis also finds that new communications technologies affect the communicative roles played by people interacting with messages mediated by posters and billboards. The thesis concludes that mediating poster and billboard marketing messages over as short a time space as possible is not prescriptive to the successful reception of that message even in an age of information overload. Further, the thesis advances multimodal discourse methodology by introducing a new methodological concept - the communicative space. Finally, implications for both pedagogy and commercial practice are identified and suggestions for future research are outlined.
Keywords: Attention; Multimodality; Modal density; Site of engagement